"The Effect of Neglecting Individual Learning Differences on the Academic Performance of Gifted and Struggling Iraqi EFL Students in Middle School" (Journal of Imam Al-Kadhim College, 2025)
This study explores the impact of neglecting individual learning differences on the academic performance of Iraqi students learning English as a foreign language (EFL) in intermediate schools, with a focus on both gifted and struggling learners. As English language education gains prominence in Iraq's educational system, addressing learner diversity becomes essential for equitable and effective instruction. The research employs a mixed-methods approach involving standardized test data, teacher interviews, and classroom observations to assess the outcomes of undifferentiated teaching. Findings reveal that neglecting individual learning styles and abilities significantly hampers academic progress, particularly among students at the two extremes of the performance spectrum. The study advocates for the adoption of differentiated instructional strategies to enhance both engagement and achievement in EFL classrooms.
Keywords: Individual learning differences, EFL, academic performance, differentiated instruction, Iraqi intermediate schools, gifted learners, struggling students